Creation of a device for producing semi-coke (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses an improvement to the mechanism for unloading finished products into a semi-coke receiving device. A device for producing semi-coke is considered. In existing devices, unloading finished products (semi-coke) is done manually, which is a labor-intensive process. The purpose of this article is to expedite the unloading of finished products into the semi-coke receiving device. To achieve this, a self-draining window for unloading finished products is provided at the bottom of the receiving device. The self-draining window is installed in a fixed guide device in the semi-coke receiving device. To unload the finished product, the self-draining window, installed in the guide device, must be lifted, at which point the unloading process begins. The products from the semi-coke receiving device are intended for use in the thermal power sector of the Republic.
Keywords: devices for producing semi-coke, unloading mechanism, coal, semi-coke, guide, self- draining window